Something old, something new: Path dependence and path creation during the early stage of a project. Issue 5 (July 2017) - Aaltonen, Kirsi; Ahola, Tuomas; Artto, Karlos
Abstract: Urban renewal projects involve several public and private stakeholders whose interaction during the project's early stage determines the scope of the project. Prior research has conveyed a somewhat ahistorical view of this early stage, based on the assumption that abundant design options are available to stakeholders. This study of a multi-stakeholder project, focused on the renewal of the commercial center of the historic garden city of Tapiola, seeks to increase understanding of processes of path dependence and path creation during the project's early stage. The findings show how a project and its stakeholders can be locked into a path that is affected by the stakeholders' shared history. The findings further reveal how external triggering events, emergent stakeholder dynamics, and active individual agency contribute to change in the project's goals, enabling breaking of the shared path and the gradual creation of a new path. Highlights: The paper advances understanding of path dependence and path creation during the early stage of multi-stakeholder projects. In the empirical study, specific path dependence and path creation processes are identified. The findings show that a project may have been locked to a pre-existing historical path already during its early stage. Changes in the project's stakeholder network can trigger radical changes that redirect the project to a new development path. The research provides new knowledge to the management of the project's early stage. This is done by theorizing on research of project stakeholders, path dependence, and path creation.